Tribromo melamine-catalyzed one-pot synthesis of a series of 4-aryl-4, 5-dihydro-1H-indeno[1, 2-b]pyridine derivatives. Issue 5 (1st September 2016) - Sudhan, Prasanna Nithiya; Ghashang, Majid; Mansoor, Syed Sheik
Abstract: A simple and efficient synthesis of 4-aryl-4, 5-dihydro-1 H -indeno[1, 2- b ]pyridine derivatives was achieved in one pot via a four-component cyclocondensation of aromatic aldehydes, 1, 3-indanedione, β -ketoesters and ammonium acetate in the presence of tribromomelamine (TBM) as the catalyst under neat conditions. The present approach offers several advantages, such as shorter reaction times, higher yields, low cost, simple work-up and easy purification compared with the other available methods.